104 EFFECTIVENESS OF 2014 ESC HCM RISK-SCD SCORE IN PREDICTION OF APPROPRIATE ICD SHOCK. (15th December 2022) - Buongiorno, Antonia Luisa; Blandino, Alessandro; Bianchi, Francesca; Masi, Andrea Sibona; Mabritto, Barbara; Luceri, Stefania; Bongioanni, Sergio; De Rosa, Catia; Parrini, Iris; Tommasello, Antonino; Grossi, Stefano; Musumeci, Giuseppe
Abstract: Background: Since 2014, European Guidelines have recommended using a novel clinical risk prediction model, called the HCM Risk-SCD, to identify which patients with hypertrophic cardiomyopathy (HCM) who are at higher risk for sudden cardiac death (SCD) and would benefit most from having a prophylactic cardioverter defibrillator (ICD) implantable. In recent years, evidence has called into question the effectiveness of this model in patient selection. Material and Methods: Data from consecutive patients with HCM and ICD who were followed at our Cardiology Department from January 2000 to January 2022 were retrospectively collected. Results: Among 702 HCM patients, 52 (7%) received an ICD (female, 31%; mean age at implantation, 49 ± 20; S-ICD, 13%; single-chamber ICD, 50%). Of them, 7 (13%) patients were implanted for secondary prevention while 45 (87%) for primary prevention. Out of the 45 primary prevention patients, 7 (16%) experienced 8 appropriate shocks (AS) while 10 (22%) had 15 inappropriate shocks (IS), during a mean follow up of 8 ± 5 years. Overall, mean HCM Risk-SCD score was 6.8 ± 4.7. Patients with AS showed a non-significant higher risk score when compared to non-AS subjects (7.1 ± 5.4 vs 4.8 ± 5.1, p=0.27). By stratifying study population according to pre-established and clinically adopted HCM Risk-SCD score cut-off (such as < 4 vs. > or = 4), we failed to highlight any significant difference in term of AS between groups. Indeed, out of 10 (22%) patients with HCM Risk-SCD score < 4, 3 (7%) experienced AS, while among 35 (78%) patients with HCM Risk-SCD score > or = 4, 4 (9%) had AS (30% vs. 11%, p=0.17). Conclusions: The HCM Risk-SCD score does not seem to be able to predict the occurrence of life-threatening ventricular arrhythmias and AS in HCM patients. Our data highlight the need to elaborate a new score in order to improve SCD risk stratification and better select patients for ICD implantation.